MANAJEMEN PROGRAM MADRASAH RAMAH ANAK (MRA) DI MADRASAH TSANAWIYAH NEGERI 3 BANYUWANGI - Asfia, Anadila Shinta (Program Studi Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2024)
Child-Friendly Madrasah (CFM) is a program that aims to create a safe, clean, healthy, and environmentally caring and cultured condition in madrasah. This program is designed to fulfill the rights and protect children from violence, discrimination, and other mistreatment. The focus of this research is: 1) how is the preparation of the CFM program at MTsN 3 Banyuwangi, 2) how is the planning of the CFM program at MTsN 3 Banyuwangi, 3) how is the implementation of the CFM program at MTsN 3 Banyuwangi, 4) how is the monitoring, evaluation, and reporting of the CFM program at MTsN 3 Banyuwangi. This research uses a qualitative approach with data collection techniques of observation, interviews and documentation. The results of this research are: 1) the preparation of the CFM program at MTsN 3 Banyuwangi was carried out by socializing the fulfillment of children's rights and protection, conducting child consultations, building commitment to developing CFM, forming an CFM Implementation Team, and identifying existing potentials, capacities, vulnerabilities, and threats, 2) the planning of the CFM program at MTsN 3 Banyuwangi was carried out by determining the objectives of CFM implementation, environmental analysis, and integrating existing policies, programs and activities, 3) the implementation of the CFM program at MTsN 3 Banyuwangi was carried out by optimizing madrasah resources, establishing cooperation with external parties, and fulfilling the 6 indicator components of CFM which consist of CFM policies, training for educators and education personnel, curriculum implementation, CFM facilities and infrastructure, child participation, and parental participation, 4) monitoring of the CFM program at MTsN 3 Banyuwangi is carried out daily by all education personnel, evaluation is carried out every time there is a meeting at least twice a month, and reporting is reported to the CFC (Child-Friendly City) Task Force Kemenag Kabupaten Banyuwangi which is done once a year.